Daya Penyembuhan Luka Bakar Fraksi Tak Larut N-Heksana dari Ekstrak Etanol Daun Seligi (Phyllanthus buxifolius Muell Arg) pada Kelinci - Siwi Hastuti (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2023)
Research has been carried out on seligi leaves (Phyllanthus buxifolius Muell. Arg.) as analgesic, antipyretic and anti-inflammatory both extracts and their fractions. However, no research has been conducted on the effects of healing burns from the n-hexane fraction of the ethanol extract of Seligi leaves. This study aims to determine the healing potency of n-hexane insoluble fraction burns from ethanol extract of Seligi leaves on rabbits. The research involved handling simplicia, extraction by maceration, fractionation with n-hexane and testing the activity of healing burns on rabbits. Observations were made by measuring the diameter of the dry wound for seven days at the burn site that had been smeared with the test preparation. Seligi leaf test preparation at a concentration of 20% compared to the positive control. The measured dry wounds are used to calculate wet wounds by subtracting the initial wound from the dry wound. The diameter of a wet wound is used to calculate the value of AUC (Area Under Curve) and %DPL (Percentage of Wound Healing Power). The percentage of DPL if the data is normally distributed and homogeneous, then statistically analyzed using the independent t test method to determine the level of significance between treatments. The n-hexane insoluble fraction from the ethanol extract of Seligi leaves with a concentration of 20% had a healing effect on burns in rabbits of (26.91 ± 2.10)% and positive controls gave healing of (28.32 ± 3.20)%, both of which were not has a significant difference.